Fetal growth in Peruvian newborns - Ticona Rendón, Manuel (2015)
OBJECTIVE: To determine intrauterine fetal growth curves in a selected group of Peruvian newborns. DESIGN: Descriptive, transversal study. SETTING: Ministry of Health hospitals, Peru. PARTICIPANTS: Live newborns. INTERVENTIONS: We enrolled successive live newborns attended during 2005, using Centro Latinoamericano de Perinatologia’s (CLAPHPO/HWO) standard weight and measuring techniques, gestational age by last menstrual period, excluding both maternal and fetal pathology, and determining smoking and maternal malnutrition. We used median, standard deviation, 10, 50 and 90 weight, height and cephalic perimeter percentiles. Curves were drawn and smoothed using third degree polynomial adjustment by Excel program. MAIN OUTCOME MEASURES: Intrauterine growth curves according to weight, height and cephalic perimeter. RESULTS: During 2005, 99 439 infants were born at Ministry of Health’s 29 hospitals; 50 568 live newborns fulfilled selection conditions and fetal growth curves from 24 through 43 weeks of gestation were elaborated. Most representative were 39 and 40 weeks gestation (55,8%), weight average 3 295 g + 407 g and 3 400 + 421 g respectively (percentiles 10, 50 and 90 were 2 750, 3 275, 3 810 g, and 2 875, 3 385, 3 930 g, respectively). Average birth height was respectively 49,7 cm + 2,3 and 50,1 cm + 2,3, and cephalic perimeter 343 mm + 16 and 345 mm + 16. CONCLUSIONS: We present a family of intrauterine growth curves according to weight, height and cephalic perimeter in a selected group of Peruvian newborns.